In the stars - Stewart, Chantal Juanita Michelle (Department of English Language and Literature, 2015)
This is a book about the nature of reality and the illusions we embrace to smooth our paths through the vagaries of life in an uncertain world. It is about the dichotomies which exist in life and how our perceptions of life define our realities. It uses the stars, moon and sky as a tool to explore these differences by counterpoising the two main characters as having different views of the same subject. Thus Gabriel is an astronomer with a rational scientific approach to the universe while Lena, though brought up in a scientific tradition, has, through her experiences and personality, learnt to question this approach and developed a more aesthetic and mythological approach to the universe. While this is explored in the tensions between her and Gabriel, her own reality is questioned through her interaction with Kingston Ingovazana Mabilu. Although she is drawn to his philosophical views on life, in the end she has misgivings about the extremes to which these beliefs will eventually take her and is unable to commit to cultural beliefs which are so different from her own. The different perceptions are also explored in relation to ideas about health, medicine, causes of illness and their treatments. This brings into opposition the two prevalent paradigms in Southern Africa of the Western medical view and the alternative traditional view. The book tries to demonstrate how these are both valid with the characters showing justifications for their own points of view. Finally, the relationship between Lena and Gabriel focuses on the delicate fragility of relationships between people, in their attempts to understand each other, to communicate, to trust and to truly know each other. In the end, these challenges may be insurmountable. The themes of the book were inspired by the everyday dichotomies of life in Southern Africa; the different languages, religions and world views. It seemed important to explore issues of life and death, health and illness, particularly in a country where, less than a decade ago, the president of the country declared that HIV was not caused by a virus. The constructs of madness also warranted elucidation, as different cultures view these behaviours very differently. The second theme of astronomy versus mythology of the universe was inspired in part by Ben Okri in Starbook and The Famished Road, where magical realism opens up new ideas about the nature of reality in an African context. I also noted the tension between these ideas and the advanced technology of the Square Kilometre Array to be developed in South Africa. The book merely hints at the political past of South Africa but concentrates on the present paradigm of differing beliefs.